Track and Field Online Curricula Evaluation System Design for Universities Physical education - Lin, Weiliang (International Journal of Emerging Technologies in Learning (iJET), 2013)
Purpose of this paper is to perfect track and field online curricula evaluation system, improve the teaching effect evaluation in the process of teaching. Research methods: by the research technique of literature search, the expert interview, the system design, the software establishment, questionnaire survey, the mathematical statistics. Results: Firstly Home page modules--cue and Response Evaluation are fast and effective; secondly function of automatic statistic and editing of assignments, exams will benefit to assess studentsâ?? ability to understand teaching content and analysis ability, as well as to assess the working efficiency of teachers grading the homework; thirdly Forum evaluation module will automatically statistical data and save the content of teacher-student interaction; fourthly evaluation of teaching statistics offers an honest reflection on the teaching effect that are the teachersâ?? and studentsâ?? performance in the class; fifthly each module with a clear content goals, connected smoothly and easy to control knowledge points browse. Conclusion: this course evaluation module can effectively reflect the effect of the implementation of teaching content as well as the usersâ?? grasping situation; the periodical self-test will help students make an objective judgment on their study, which can promote the communication between teachers and students, and to evaluate the teaching schedule modifications constantly.